2017
DOI: 10.1002/celc.201600717
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study of Selenocystine Reactivity and Reduction at Metallic Surfaces

Abstract: The reduction of seleno-L-cystine is examined on gold and platinum electrodes in aqueous solution. The voltammetric behavior is indicative of a two-step process, in which the metallic substrate is modified by the diselenide analyte prior to observation of diffusionally controlled, proton-coupled electron transfer. X-ray photoelectron spectroscopy confirms the presence of selenium on gold foil samples that have been reductively cycled in selenocystine solution. The selenium-based surface modification, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Antimicrobial resistance remains one of the most critical public health concerns, as current medicines used to treat a variety of ailments caused by viruses, fungi, and bacteria become ineffective. Research into antimicrobial agents that subsequently do not become resistant to such microbes is thus needed to avert this crisis. Several studies have focused on silver nanoparticles for antimicrobial solutions; however, studies have indicated emerging resistance to these materials from bacterial populations as well as toxicity to human cells. One potential alternative to silver in this role is selenium, a trace element in the human body that is an essential micronutrient often found as selenocysteine, the 21st human amino acid. , Selenium nanoparticles have been shown to exhibit effective antimicrobial properties against a broad range of microorganisms including Escherichia coli and Candida albicans . Moreover, there has been an increased interest in functionalizing selenium nanoparticles using chitosan, hyaluronic acid, polyethylene glycol (PEG), pectin, and peptides, in order to improve stability and enhance biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial resistance remains one of the most critical public health concerns, as current medicines used to treat a variety of ailments caused by viruses, fungi, and bacteria become ineffective. Research into antimicrobial agents that subsequently do not become resistant to such microbes is thus needed to avert this crisis. Several studies have focused on silver nanoparticles for antimicrobial solutions; however, studies have indicated emerging resistance to these materials from bacterial populations as well as toxicity to human cells. One potential alternative to silver in this role is selenium, a trace element in the human body that is an essential micronutrient often found as selenocysteine, the 21st human amino acid. , Selenium nanoparticles have been shown to exhibit effective antimicrobial properties against a broad range of microorganisms including Escherichia coli and Candida albicans . Moreover, there has been an increased interest in functionalizing selenium nanoparticles using chitosan, hyaluronic acid, polyethylene glycol (PEG), pectin, and peptides, in order to improve stability and enhance biocompatibility .…”
Section: Introductionmentioning
confidence: 99%
“…26−28 One potential alternative to silver in this role is selenium, a trace element in the human body that is an essential micronutrient often found as selenocysteine, the 21st human amino acid. 29,30 Selenium nanoparticles have been shown to exhibit effective antimicrobial properties 31−33 against a broad range of microorganisms including Escherichia coli and Candida albicans. 32 Moreover, there has been an increased interest in functionalizing selenium nanoparticles using chitosan, 34 hyaluronic acid, 35 polyethylene glycol (PEG), 36 pectin, 37 and peptides, 38 in order to improve stability and enhance biocompatibility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2628 One potential alternative to silver in this role is selenium, a trace element in the human body that is an essential micronutrient often found as selenocysteine, the 21st human amino acid. 29,30 Selenium nanoparticles have been shown to exhibit effective antimicrobial properties 31–33 against a broad range of microorganisms including Escherichia coli and Candida albicans . 32 Moreover, there has been an increased interest in functionalising selenium nanoparticles using chitosan, 34 hyaluronic acid, 35 polyethylene glycol (PEG), 36 pectin 37 and peptides, 38 in order to improve stability and enhance biocompatibility.…”
Section: Introductionmentioning
confidence: 99%